Sex-specific association between serum α-klotho levels and sleep disturbances in the elderly: a cross-sectional study - Lu Liu; Tao Xu; Xiaolan Gao; Xianying Lei; Qinxue Hu (European Journal of Medical Research)
Abstract Background Sleep disturbances (SD) exhibit a high prevalence among older adults and exert considerable influence on cardiovascular health, quality of life, and other facets of well-being. α-Klotho, an anti-aging factor that diminishes with advancing age, has been implicated in a multitude of age-related conditions. However, the relationship between SD and α-klotho levels in the elderly remains inadequately investigated, and potential sex-specific differences in this association warrant further exploration. Methods This study utilized data from the National Health and Nutrition Examination Survey (NHANES) to initially investigate the association between α-klotho levels and SD, with analyses conducted separately for both sexes. In addition, the relationship was further delineated using restricted cubic spline (RCS) curves. Results A total of 5,957 elderly adults participated in this study, revealing a prevalence of SD at 29.5%. Notably, females exhibited a higher prevalence of SD compared to men (33.6% for females vs. 25.3% for males). After adjusting for covariates, higher α-klotho levels were hypothesized to be associated with a decreased incidence of SD. Differences also existed between sexes, as demonstrated by a significant correlation between serum α-klotho and SD in females, but not in males. Results from the RCS analysis indicated a negative and nonlinear relationship between α-klotho levels and SD, consistent across both sexes and the general population. Conclusions The findings of the current study revealed a negative association between α-klotho levels and the development of SD in the elderly population, with notable sex-specific differences.